Investigating The Effects of Body Weight and Physical Activities on The Electrical Generation of Piezoelectric Generator - Lo N.Z.X.; Mohamed H.; Rafaai Z.F.M.; Junoh H.; Zainal B.S.; Shamsuddin A.H. (American Institute of Physics, 2025)
This research paper investigates the effects of body weight and physical activities on the electrical generating capability of piezoelectric generators. The objectives of this paper include investigating the application of piezoelectric generators in converting mechanical energy from human activities to generate electricity, assessing the effect of active and sedentary activities on piezoelectric generation, and evaluating if different body weight affects the electrical output. To accomplish these objectives, two piezoelectric generators were built. The first generator was built to harvest electrical energy from jumping, walking, and running, and the second was built to harvest electrical energy from sitting. Next, an Arduino device was programmed as an oscilloscope to track the power output from the piezoelectric device. The experiment's sample size was five participants, with three males and two females. The results of the investigation concluded that active activities are more capable of producing higher amounts of power than sedentary activities. However, fatigue is observed when doing active activities, whereas sedentary activities do not show any sign of fatigue. Furthermore, this experiment reported that the body weight factor does not significantly affect the final power generation due to a possible limitation of the piezoelectric material. ? 2024 American Institute of Physics Inc.. All rights reserved.